Ribosomes of the extremely thermophilic eubacterium Thermotoga maritima are uniquely insensitive to the miscoding-inducing action of aminoglycoside antibiotics. - Londei, P (1988)
Poly(U)- and poly(UG)-programmed cell-free systems were developed from the extreme thermophilic, anaerobic eubacterium Thermotoga maritima, and their susceptibility to aminoglycoside and other antibiotics was assayed at a temperature (75 degrees C) close to the physiological optimum (80 degrees C) for cell growth and in vitro polypeptide synthesis, using a Bacillus stearothermophilus system as the reference. The synthetic capacity of the Thermotoga assay mixture was abolished by the eubacterium-targeted drugs chloramphenicol, thiostrepton, and kirromycin. However, streptomycin, the disubstituted 2-deoxystreptamines (kanamycin, gentamicin, neomycin, and paromomycin), and the monosubstituted 2-deoxystreptamine (hygromycin) all failed to promote translational misreading of poly(U) on Thermotoga ribosomes; they also failed to block polyphenylalanine synthesis at a low (less than 10(-4) M) concentration and did not inhibit Thermotoga cell growth at a high (10 micrograms/ml) concentration even though Thermotoga ribosomes possess the 16S rRNA sequences required for aminoglycoside action. In contrast to the other eubacteria, Thermotoga elongation factor G was also refractory to the steroid inhibitor of peptidyl-tRNA translocation fusidic acid.